(untitled) (Research, Society and Development, 2024)
Introduction: Experimental animal models have an important role in the improvement of knowledge about diverse pathologies, being mice the main experimental animals, used to learn about those diseases. There’s a very important significance of oophorectomy in experimentation, and because of that we studied to develop a new technique based on minimally invasive principles to obtain better outcomes and fewer surgical risks. Objectives: Develop and describe a new minimally invasive surgical method using a hook to perform oophorectomy in mice, develop a new oophorectomy-specific hook and evaluate operating parameters. Methods: For the research were used 30 female Wistar mice, young adults, weighing between 200-250g. During the procedure two 0,5cm incisions were performed, where the proper hook was inserted to search the ovary, when found, it was repaired and ligated and the procedure was repeated on the other side. Results and Discussion: The new surgical technique, using the hook, demonstrated beneficial because it presented: 1) Smaller incision to access the ovaries 2) Lower surgical time 3) Good wound evolution in a 7 days period 4) 0% (zero percent) mortality rate and 5) good performance and recovery after surgery. Conclusion: The development of a new surgical hook for oophorectomy in mice, enabled a minimally invasive procedure with two 0,5 cm incision (smallest size in literature), also a consequent faster surgical time and better postoperative conditions, being developed a new surgical technique with better outcomes and less complications.